2007
DOI: 10.1007/s11240-007-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic instabilities induced by tissue culture in wild barley (Hordeum brevisubulatum (Trin.) Link)

Abstract: A simple tissue culture protocol was developed for efficient plant regeneration from young inflorescence-derived calli in wild barley, Hordeum brevisubulatum (Trin.) Link, an important pasturage grass. Genetic and epigenetic instabilities in the regenerated plants (regenerants) were assessed by three molecular markers AFLP, S-SAP and MSAP. Two pools of calli derived from young inflorescences of a single donor plant and 44 randomly chosen regenerants were subjected to AFLP analysis. Results showed that 74 out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 50 publications
5
49
0
1
Order By: Relevance
“…Similarly, low levels of methylation variation were found in freesia somatic seedlings derived from short-term cultures (Gao et al 2010) and pea long-term multiple shoot cultures (Smýkal et al 2007). Many studies with methylation-sensitive molecular markers that reported a high level of epigenetic variation reported no effect on phenotype or morpho-agronomic traits (Bednarek et al 2007;Li et al 2007;Schellenbaum et al 2008;Fiuk et al 2010). Methylation changes contribute poorly to global estimations when they do not occur at high frequencies (Smulders and Klerk 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low levels of methylation variation were found in freesia somatic seedlings derived from short-term cultures (Gao et al 2010) and pea long-term multiple shoot cultures (Smýkal et al 2007). Many studies with methylation-sensitive molecular markers that reported a high level of epigenetic variation reported no effect on phenotype or morpho-agronomic traits (Bednarek et al 2007;Li et al 2007;Schellenbaum et al 2008;Fiuk et al 2010). Methylation changes contribute poorly to global estimations when they do not occur at high frequencies (Smulders and Klerk 2011).…”
Section: Discussionmentioning
confidence: 99%
“…taylor et al (18) indicated that there might be epigenetic changes although there are few polymorphisms. li et al (11) searched for genetic and epigenetic similarities in tissue culture regenerants of wild barley (Hordeum brevisubulatum (trin.) link) with various markers such as AFlP, S-SAP and MSAP.…”
Section: Resultsmentioning
confidence: 99%
“…Aversano et al (2009) demonstrated that under in vitro culture conditions Solanum genotype affects the integrity of the genome and absence of polymorphism at plastid level confirms the greater genetic stability of cytoplasmic DNA. Li et al (2007) demonstrated genetic and epigenetic instabilities induced by tissue culture in wild barley using AFLP, S-SAP and MSAP markers. Based on our results, it is concluded that AFLP is the best method followed by SSR, ISSR and RAPD for detection of genetic stability of in vitro conserved potato microtubers.…”
Section: Discussionmentioning
confidence: 99%
“…AFLP can be generated for any organism without initial investment in primer/probe development and sequence analysis. Like RAPD and ISSR, in the past SSR and AFLP markers have also been used to detect genetic fidelity in many plants such as Elaeis guineensis (Matthes et al 2001), Hordeum brevisubulatum (Li et al 2007), Solanum tuberosum (Zarghami et al 2008;Dann and Wilson 2011), Pinus pinaster (Marum et al 2009) and Ocotea catharinensis (Hanai et al 2010). The aim of the present study was to assess the genetic stability of in vitro conserved potato microtubers by RAPD, ISSR, SSR and AFLP markers and also confirmed in vitro conservation protocol.…”
Section: Introductionmentioning
confidence: 98%